2007
DOI: 10.1159/000096930
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Scaffolds for Reconstruction of the Urinary Tract by Tissue Engineering

Abstract: Introduction: Tissue engineering is an important and expanding field in reconstructive surgery. The ideal biomaterial for urologic tissue engineering should be biodegradable and support autologous cell growth. We examined different scaffolds to select the ideal material for the reconstruction of the bladder wall by tissue engineering. Materials and Methods: We seeded mouse fibroblasts and human keratinocytes in a co-culture model on 13 different scaffolds. The cell-seeded scaffolds were fixed and processed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 51 publications
2
30
0
3
Order By: Relevance
“…To date, decellularized natural (based on bladder or small intestine submucosa) and synthetic scaffolds have been proposed. [8][9][10] Although natural scaffolds were shown to have a therapeutic efficacy, application of synthetic scaffolds is preferential due to the possibility of producing individualized forms with defined physicochemical characteristics.…”
mentioning
confidence: 99%
“…To date, decellularized natural (based on bladder or small intestine submucosa) and synthetic scaffolds have been proposed. [8][9][10] Although natural scaffolds were shown to have a therapeutic efficacy, application of synthetic scaffolds is preferential due to the possibility of producing individualized forms with defined physicochemical characteristics.…”
mentioning
confidence: 99%
“…Bladder acellular matrix may be the most extensively used scaffold in tissue engineering. It has been demonstrated that the cells have the ability to induce the ingrowth of urothelium, smooth muscle, endothelium and nerve cells (53). Perhaps the greatest advantage of the use of acellular matrices is the ability to provide a method of neovascularisation following graft insertion, promoting graft survival.…”
Section: Naturally Derived Matricesmentioning
confidence: 99%
“…The use of nanotechnology permits the development of a graft that can be manipulated to produce characteristics with definitive properties in order to promote optimal cell proliferation and tissue differentiation (53). A previous study investigated the effect of surface roughness on the interaction with matrix proteins (81).…”
Section: Naturally Derived Matricesmentioning
confidence: 99%
“…cellular proliferation [1,5], differentiation [6][7][8], deposition of new structural proteins [9,10] and ultimately the regeneration of functional tissue [4,11,12]. Traditionally, methods such as NMR, FTIR and X-Ray spectroscopy have been used to assess biomaterials at the molecular level [13][14][15][16][17], while SEM and TEM have been invaluable tools for characterizing the three dimensional morphology of biomaterial scaffolds [5,[18][19][20][21][22][23]. Histology and immunostaining as well as assays for determining the expression levels of specific proteins are often used to assess how scaffolds interact with cells as tissues develop [5,10,18,20,[22][23][24].…”
Section: Competing Interest Statementmentioning
confidence: 99%
“…Traditionally, methods such as NMR, FTIR and X-Ray spectroscopy have been used to assess biomaterials at the molecular level [13][14][15][16][17], while SEM and TEM have been invaluable tools for characterizing the three dimensional morphology of biomaterial scaffolds [5,[18][19][20][21][22][23]. Histology and immunostaining as well as assays for determining the expression levels of specific proteins are often used to assess how scaffolds interact with cells as tissues develop [5,10,18,20,[22][23][24]. While all of these approaches provide sensitive and specific data, they are invasive.…”
Section: Competing Interest Statementmentioning
confidence: 99%